The autophagy gene ATG8 affects morphogenesis and oxidative stress tolerance in Sporisorium scitamineum - Bin ZHANG; Guo-bing CUI; Chang-qing CHANG; Yi-xu WANG; Hao-yang ZHANG; Bao-shan CHEN; Yi-zhen DENG; Zi-de JIANG (Journal of Integrative Agriculture, 2019)
The basidiomycetous fungus Sporisorium scitamineum causes sugarcane smut that leads to severe economic losses in the major sugarcane growing areas in China, India and Brazil, etc. Autophagy is a conserved pathway in eukaryotes for bulk degradation and cellular recycling, and was shown to be important for fungal cell growth, development, and pathogenicity. However, physiological function of autophagy has not been studied in S. scitamineum. In this study, we identified a conserved Atg8 protein, named as SsAtg8 and characterized its function. Our results showed that autophagy was blocked in the ssatg8Δ mutant, in nitrogen starvation. The ssatg8Δ mutant formed pseudohypha frequently and was hypersensitive to oxidative stress. However, mating or filamenation was unaffected in the ssatg8Δ mutant in vitro. Overall we demonstrate that autophagy is dispensable for S. scitamineum mating/filamentation, while critical for oxidative stress tolerance and proper morphology in sporidial stage.